2016
DOI: 10.5334/ijic.2497
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Prudent Dementia Care (Palliare): An International Policy and Practice Imperative

Abstract: This paper examines the provision of integrated advanced dementia care within seven European countries and critically reviews the potential contribution of the Prudent Healthcare perspective as a starting point for reform. Progressive efforts to innovate, promote quality and integrate care are tempered with the reality of resource constraints. Some policy makers in Europe and North America have turned their attention to the principles of Prudent Healthcare as a potential mechanism to maximise benefits for pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
0
22
0
1
Order By: Relevance
“…Dementia care is provided by a wide variety of professionals from different disciplines (Hvalič Touzery et al, 2015), many of whom lack education about working with people with dementia (Gandesha et al, 2012;Ibrahim and Davis, 2013;Adler et al, 2015;Hanson et al, 2016;Tolson et al, 2016). This is particularly acute amongst those professionals (nurses, social workers, psychologists, dieticians, nurses, occupational therapists and physiotherapists) who work outside mental health (Pulsford et al, 2007;Griffiths et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dementia care is provided by a wide variety of professionals from different disciplines (Hvalič Touzery et al, 2015), many of whom lack education about working with people with dementia (Gandesha et al, 2012;Ibrahim and Davis, 2013;Adler et al, 2015;Hanson et al, 2016;Tolson et al, 2016). This is particularly acute amongst those professionals (nurses, social workers, psychologists, dieticians, nurses, occupational therapists and physiotherapists) who work outside mental health (Pulsford et al, 2007;Griffiths et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The fourlevel framework outlines the knowledge, skills and understanding all health and social care staff should have to support people with dementia, their families and friends. There has also been a European Best Practice Statement developed to support interdisciplinary healthcare professionals to deliver advanced dementia care (Tolson et al, 2016). Both of these are useful for supporting the development of practice however it is up to the discretion of employers whether and to what extent they embed these frameworks into the education and training of staff.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, needs assessment separates the evaluation of different people (professionals, family caregiver, and person with dementia) (Callahan et al, 2006;Johansson, Eklund, & Gosman-Hedstrom, 2010). The assessment of needs should be taken into account the past life experiences, cultural background, preferences, and identities (Holmerova et al, 2016) and joint together the recipient of needs, the caregivers, and the professionals (Dinand, Nover, Holle, Zischka, & Halek, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that planning for advanced dementia is often not undertaken (Holmerova et al, 2016;Tolson et al, 2016), due to a lack of consistent information. A comprehensive assessment of the healthcare needs is indispensable to decisions related to the provision of quality care.…”
Section: Con Clus Ionmentioning
confidence: 99%
See 1 more Smart Citation